WOMEN ISSUES IN TWO SHORT STORIES BY RATNA INDRASWARI IBRAHIM: A STUDY OF COMPARATIVE LITERATURE TOWARD TWO SHORT STORY; âRAMBUTNYA JUMINTENâ AND âBAJUâ - Mardani, Putri Bestari; Suprasti, Devi; Aratika, Juni (Kajian Linguistik dan Sastra, 2017)
Â TheÂ  issueÂ  ofÂ  womenâsÂ  lifeÂ  hasÂ  alwaysÂ  beenÂ  anÂ  interestingÂ  topicÂ  toÂ  be discussed. This kind of issue has been widely delivered by story writers, which is by placing women as the main character in his/her work. It aims to convey the results of their thoughts in the form of literary works. As already been known, literaryÂ  worksÂ  areÂ  oneÂ  ofÂ  anÂ  essentialÂ  container Â toÂ  describeÂ  theÂ  reflexivityÂ  of society.Â  SensitiveÂ  issuesÂ  couldÂ  beÂ  freelyÂ  expressedÂ  inÂ  literaryÂ  works.Â  AsÂ  an exampleÂ  isÂ  theÂ  issueÂ  ofÂ  womenÂ  whichÂ  isÂ  describedÂ  inÂ  shortÂ  storiesÂ  formÂ  and published through the mass media.Â TheÂ  aimsÂ  ofÂ  thisÂ  paperÂ  areÂ  toÂ  explainÂ  theÂ  formsÂ  ofÂ  problemsÂ  orÂ  issues revolving women that are presented in the âBajuâand âRambutnya Jumintenâtext by Ratna Indraswari Ibrahim. This study uses the theory of feminism by Simone de Beauvoir. Beauvoir suggests that women are considered as the second-class citizens or as the second sex due to patriarchal power, a notion that can lead to gender inequality (Kuntowijoyo 1987: 136).Â Based on the study, it was found that both texts reveal various forms of womenâs issues, which are patriarchy and gender constructions. Both traditional women and an empress with a high social position experience the same issue. Although the two female figures were trying to speak up, they are being ignored. This is because there is a widely known stereotype that states that women are emotional and irrational, so women are considered unable to manage their own lives and are not suitable to speak in a public sphere.Â Keyword:Â  comparativeÂ  literature,Â  feminism,Â  shortÂ  story,Â  RatnaÂ  Indraswari, women issues.